Screening and brief interventions for adolescent alcohol use disorders presenting through emergency departments: a research programme including two RCTs - Paolo Deluca; Simon Coulton; Mohammed Fasihul Alam; Sadie Boniface; Kim Donoghue; Eilish Gilvarry; Eileen Kaner; Ellen Lynch; Ian Maconochie; Paul McArdle; Ruth McGovern; Dorothy Newbury-Birch; et al. (NIHR Journals Library, 2020)
Background: Alcohol consumption and related harm increase steeply from the ages of 12-20 years. Adolescents in the UK are among the heaviest drinkers in Europe. Excessive drinking in adolescents is associated with increased risk of accidents, injuries, self-harm, unprotected or regretted sex, violence and disorder, poisoning and accidental death. However, there is lack of clear evidence for the most clinically effective and cost-effective screening and brief interventions for reducing or preventing alcohol consumption in adolescents attending emergency departments (EDs). Objectives: To estimate the distribution of alcohol consumption, alcohol-related problems and alcohol use disorders in adolescents attending EDs; to develop age-appropriate alcohol screening and brief intervention tools; and to evaluate the clinical effectiveness and cost-effectiveness of these interventions. Design: The research has been conducted in three linked stages: (1) a prevalence study, (2) intervention development and (3) two linked randomised controlled trials (RCTs). Setting: Twelve EDs in England (London, North East, and Yorkshire and The Humber). Participants: A total of 5376 participants in the prevalence study [mean age 13.0 years, standard deviation (SD) 2.0 years; 46.2% female] and 1640 participants in the two linked RCTs (mean age 15.6 years, SD 1.0 years; 50.7% female). Interventions: Personalised feedback and brief advice (PFBA) and personalised feedback plus electronic brief intervention (eBI), compared with alcohol screening alone. These age-appropriate alcohol interventions were developed in collaboration with the target audience through a series of focus groups and evaluations during stage 2 of the research programme and following two literature reviews. Main outcome measures: Total alcohol consumed in standard UK units (1 unit = 8 g of ethanol) over the previous 3 months at 12-month follow-up, assessed using the Alcohol Use Disorders Identification Test, Consumption (3 items) (AUDIT-C). Results: In the prevalence study, 2112 participants (39.5%) reported having had a drink of alcohol that was more than a sip in their lifetime, with prevalence increasing steadily with age and reaching 89.5% at the age of 17 years. The prevalence of at-risk alcohol consumption was 15% [95% confidence interval (CI) 14% to 16%] and the optimum cut-off point of the AUDIT-C in identifying at-risk drinking was ≥ 3. Associations of alcohol consumption and early onset of drinking with poorer health and social functioning were also found. In the RCT, the analysis of the primary outcome (average weekly alcohol consumption at month 12) identified no significant differences in effect between the three groups in both trials. In the high-risk drinking trial, the mean difference compared with control was 0.57 (95% CI -0.36 to 1.70) for PFBA and 0.19 (95% CI -0.71 to 1.30) for eBI. In the low-risk drinking trial, the mean difference compared with control was 0.03 (95% CI -0.07 to 0.13) for PFBA and 0.01 (95% CI -0.10 to 0.11) for eBI. The health economic analysis showed that eBI and PFBA were not more cost-effective than screening alone. Conclusions: The ED can offer an opportunity for the identification of at-risk alcohol use in adolescents. A simple, short, self-completed screening instrument, the AUDIT-C, is an effective tool for identifying adolescents who are at risk of alcohol-related problems. Associations of alcohol consumption and earlier onset of drinking with poorer health and social functioning were observed in the prevalence study. The trials were feasible to implement and exceeded the recruitment target and minimum follow-up rates. However, PFBA and eBI were not found to be more effective than screening alone in reducing or preventing alcohol consumption in 14- to 17-year-olds attending EDs. Limitations and future work: Only one-third of participants engaged with the application program; this is likely to have limited the effect of the intervention. We recommend that future research should focus on methods to maximise engagement with digital interventions and evaluate the effect of such engagement on clinical outcomes. Trial registration: Current Controlled Trials ISRCTN45300218. Funding: This project was funded by the National Institute for Health Research (NIHR) Programme Grants for Applied Research programme and will be published in full in Programme Grants for Applied Research; Vol. 8, No. 2. See the NIHR Journals Library website for further project information.